PERANAN KOMUNIKASI INTERPERSONAL DI LINGKUNGAN KELUARGADALAM MEMBENTUK KESEHATAN MENTAL PADA ANAK USIA DINI - Mia Tania; Enung Nurhayati, Deli Lutfhi Rahman, Nasmi Abdurrahman (JOURNAL OF COMMUNITY DEDICATION, 2024)
Family is the smallest social unit in society which is able to provide the basic foundation for children's physical, emotional, social and moral development, as well as covering other more fundamental aspects, such as identity formation and providing emotional support. Family is the first place where children learn about love, security, trust, and how to resolve conflicts. However, the role of the family in individual formation does not always run smoothly. Social, economic and cultural changes around them can influence family dynamics. The quality of interpersonal communication influences children in responding to challenges, managing emotions, and building social relationships with other people outside the family sphere. This paper aims to examine in more depth the role and influence of interpersonal communication in the family on the formation of children's mental health. By understanding these dynamics, it is hoped that effective strategies can be found to improve the quality of communication within the family, so that it can support children's growth and development optimally, both physically and mentally.